Optimizing Sago Land Utilization by Intercropping with Eggplants, A Study at Tanjung Peranap Village, Meranti Island, Riau, Indonesia - Zuhro, Fatimatus; Djoefrie, M.H. Bintoro (Department of Agronomy and Horticulture, IPB University, 2020)
Sago palms are the main food crops in eastern part of Indonesia. Sago productivity can reach 20 to 40 per ha per year, and the trees can be harvested when they are 10 years of age. Due to long duration before harvesting it is important that sago growers could grow annual food crops. The objective of study is to determine the growth of sago palm intercropped with eggplants, and how intercropping aff ects each crop grown as monoculture. The study was carried out from March to July 2018 at Tanjung Peranap Village, Meranti Island District, Riau Province, Indonesia. The experiment was organized in a completely randomized block design with two replications, with sago palm and eggplant as monoculture and as inter cropping. The results demonstrated that young sago palm did not suppress eggplant growth and vice versa. Therefore, eggplants can be planted between young sago palms.